2012
DOI: 10.1021/es301165p
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs Free Energy of Formation of Chlordecone and Potential Degradation Products: Implications for Remediation Strategies and Environmental Fate

Abstract: Chlordecone (C 10 Cl 10 O; CAS number 143-50-0) has been used extensively as an organochlorine insecticide but is nowadays banned under The Stockholm Convention on Persistent Organic Pollutants (POPs). A search for chlordecone-respiring organisms and choosing between reductive versus oxidative remediation tools and strategies to clean up chlordecone-polluted environments would benefit from the availability of Gibbs free energy data of chlordecone and its potential dechlorination products. Presently such data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…The volatility and solubility of 5b-hydroCLD have never been determined experimentally. From thermodynamic data, Dolfing et al (2012) have estimated that 5b-hydroCLD has a Henry's constant of 0.00284 Pa m or liquid chromatographic analysis using apolar columns (Carver and Griffith 1979;George et al 1986;Belghit et al 2015; this article, data not shown). This elution order is indeed experimental evidence that 5b-hydroCLD is more polar than CLD and so necessarily more soluble in a polar solvent like water.…”
Section: Different Physical Behaviour Of 5b-hydrocld and Cld Resultinmentioning
confidence: 91%
See 3 more Smart Citations
“…The volatility and solubility of 5b-hydroCLD have never been determined experimentally. From thermodynamic data, Dolfing et al (2012) have estimated that 5b-hydroCLD has a Henry's constant of 0.00284 Pa m or liquid chromatographic analysis using apolar columns (Carver and Griffith 1979;George et al 1986;Belghit et al 2015; this article, data not shown). This elution order is indeed experimental evidence that 5b-hydroCLD is more polar than CLD and so necessarily more soluble in a polar solvent like water.…”
Section: Different Physical Behaviour Of 5b-hydrocld and Cld Resultinmentioning
confidence: 91%
“…The coupling of this FeIII/FeII cycling to the dechlorination of chlorinated compounds has been demonstrated at lab scale (Li et al 2008(Li et al , 2009) and could work for the CLD/5b-hydroCLD redox couple. CLD/5b-hydroCLD has indeed a redox potential of +414 mV (Dolfing et al 2012), which indicates that it can act as an electron acceptor for the 'iron oxide'/FeII couples, this part of the process being merely abiotic (Fig. 3).…”
Section: Potential Formation Of 5b-hydrocld By Cld Dechlorinationmentioning
confidence: 98%
See 2 more Smart Citations
“…Nowadays, CLD is still present in soils, especially in the densely cultivated areas from south of Basse-Terre (Guadeloupe) (Cabidoche et al, 2009). Although, Fernández-Bayo et al (2013) showed the existence of CLD degrading organisms in a tropical soil (andosol) microcosm under aerobic conditions, CLD undergoes no significant or quick biotic or abiotic degradation (Dolfing et al, 2012;Levillain et al, 2012). Driven by the water cycle, CLD in soils is progressively transferred to aquatic ecosystems (Coat et al, 2011) and also in the food web because of its high K oc (Soil Organic Carbon Water Partitioning Coefficient) (15849 L/Kg), K ow (Octanol-Water Partition Coefficient) (4.5-6.0) and its affinity for lipids (Cabidoche and Lesueur-Jannoyer, 2012;Clostre et al, 2013;Sterrett and Boss, 1977;UNEP, 2005;US-EPA, 2008).…”
Section: Introductionmentioning
confidence: 99%